Video research visits for atypical parkinsonian syndromes among Fox Trial Finder participants. Issue 1 (February 2020) - Tarolli, Christopher G.; Zimmerman, Grace A.; Goldenthal, Steven; Feldman, Blake; Berk, Sarah; Siddiqi, Bernadette; Kopil, Catherine M.; Chowdhury, Sohini; Biglan, Kevin M.; Dorsey, E. Ray; Adams, Jamie L.
Abstract : Background: Use of video research visits in neurologic conditions is rising, but their utility has not been assessed in atypical parkinsonian syndromes. We sought to evaluate the diagnostic concordance between video-based vs self-reported diagnoses of multiple system atrophy, progressive supranuclear palsy, dementia with Lewy bodies, and corticobasal syndrome. We also assessed patient satisfaction with video-based visits. Methods: We conducted a study of video-based research visits in individuals with an atypical parkinsonian syndrome enrolled in The Michael J. Fox Foundation's Fox Trial Finder. Participants completed a recorded real-time video visit with a remote evaluator who was blinded to the participant's self-reported diagnosis. The investigator conducted a structured interview and performed standard assessments of motor function. Following the visit, the investigator selected the most likely diagnosis. The recorded visit was reviewed by a second blinded investigator who also selected the most likely diagnosis. We evaluated diagnostic concordance between the 2 independent investigators and assessed concordance between investigator consensus diagnosis and self-reported diagnosis using Cohen's kappa. We assessed participant satisfaction with a survey. Results: We enrolled 45 individuals with atypical parkinsonian syndromes, and 44 completed the investigator-performed video assessment. We demonstrated excellent concordance in diagnosis between the investigators (κ = 0.83) and good reliability of self-reported diagnosis (κ = 0.73). More than 90% of participants were satisfied or very satisfied with the convenience, comfort, and overall visit. Conclusions: Video research visits are feasible and reliable in those with an atypical parkinsonian syndrome. These visits represent a promising option for reducing burden and extending the reach of clinical research to individuals with these rare and disabling conditions.